2019
DOI: 10.1021/acsami.9b15195
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Renally Clearable Silica Nanoparticles Target Prostate Cancer

Abstract: Although important advances have been achieved in the development of radiolabeled prostatespecific membrane antigen (PSMA)-targeting ligand constructs for both diagnosis and therapy of prostate cancer (PCa) over the past decade, challenges related to off-target effects and limited treatment responses persist. In this study, which builds upon the successful clinical translation of a *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…administration) with the size decreased by 1.16 nm (from 5.52 to 4.36 nm; Prabhakar et al, 2013). A similar result was observed 48 hr after administration of PEG-coated silica NPs, where the renal clearance increase (from 64% ID to 73% ID) was caused by 2.7 nm decrease (from 6.0 to 3.3 nm) of their size (Chen et al, 2019). Gold nanoparticles also demonstrated size-dependent renal clearance.…”
Section: Enable Renal Clearancesupporting
confidence: 76%
See 1 more Smart Citation
“…administration) with the size decreased by 1.16 nm (from 5.52 to 4.36 nm; Prabhakar et al, 2013). A similar result was observed 48 hr after administration of PEG-coated silica NPs, where the renal clearance increase (from 64% ID to 73% ID) was caused by 2.7 nm decrease (from 6.0 to 3.3 nm) of their size (Chen et al, 2019). Gold nanoparticles also demonstrated size-dependent renal clearance.…”
Section: Enable Renal Clearancesupporting
confidence: 76%
“…It was found that the amount of RGD ligands conjugated to IONPs was 1.32 ± 0.24 mmol/g Fe for uIONPs with a core size of 3 nm comparing to 0.38 ± 0.05 and 0.15 ± 0.01 mmol/g Fe for IONPs with 10 and 20 nm core diameters, respectively (Figure 7f). The high loading with sub‐5 nm nanoparticles can be also applied to carry more signal emitting molecules, such as near infared (NIR) dye Cy5.5 or PET sensitive 64 Cu chelate for PET, for multi‐modal imaging to enhance the sensitivity of the detection (Chen et al, 2019; Ning et al, 2017).…”
Section: Improved Properties and Functionalitiesmentioning
confidence: 99%
“…With respect to imaging, renal clearance is a double-edged sword, as rapid clearance will limit time for both passive and active tissue targeting, but will simultaneously reduce background signal and reduce concerns over bioaccumulation, biopersistence and toxicity. For example, "ultrasmall," <10 nm nanoparticles are being investigated as targeted imaging agents that accumulate rapidly in tissues, but also undergo rapid renal elimination, allowing for high signal to noise (F. Chen et al, 2019).…”
Section: Barriers To Tissue Accumulation and Targetingmentioning
confidence: 99%
“…[2][3][4][5][6] However, only a few of these nanodrug candidates reach the clinical trials. Besides Fe-raheme®, an iron oxide USNP used for chronic kidney disease, only Nanotherm® and Cornell dots 4 have been approved by FDA (Food and Drug Administration) and AGuIX® 5 by ANSM (Agence Nationale de Sécurité du Médicament, French equivalent of FDA), for first-in-human clinical trials in cancer therapy. As pointed out by K. Zarschler et al, 6 one of the main issues limiting the passage in the clinic of these promising nano-objects is the lack of methods allowing their physicochemical characterization, particularly in biological media, to answer regulatory agencies requirements.…”
mentioning
confidence: 99%